x+1/2=x-1/3+1/4

Simple and best practice solution for x+1/2=x-1/3+1/4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+1/2=x-1/3+1/4 equation:


x+1/2=x-1/3+1/4

We simplify the equation to the form, which is simple to understand
x+1/2=x-1/3+1/4

We move all terms containing x to the left and all other terms to the right.
+1x-1x=-0.33333333333333 + 0.25-0.5

We simplify left and right side of the equation.
0x=-0.58333333333333

0=-0.58333333333333

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| 5x+60=540 | | A=10A-20 | | 2x+8x?10=0 | | 2x+12=98 | | 20-x=x-14 | | 0,8x+6=x | | x+0,88x=47 | | -3x+3=-1 | | 3(2x-5)-2(x-3)=3(x+1) | | 2^x=64 | | 2^x=64-5 | | 2/8x-4=8 | | K=r(n-1)+r^ | | k^n=r(r-1+n) | | 3x-6=-2+4 | | 2(3x-1)+3(x+20.6)=2(3)+6(2x+4) | | 2(3x-1)+3(x+20.7)=2(3)+6(2x+4) | | 2(3x-1)+3(x+20.8)=2(3)+6(2x+4) | | 2(3x-1)+3(x+21.5)=2(3)+6(2x+4) | | 2(3x-1)+3(x+21)=2(3)+6(2x+4) | | 2(3x-1)+3(x+20)=2(3)+6(2x+4) | | 2(3x-1)+3(x+33.66986432)=2(3)+6(2x+4) | | 2(3x-1)+3(x+33.669)=2(3)+6(2x+4) | | 2(3x-1)+3(x+33.66)=2(3)+6(2x+4) | | 2(3x-1)+3(x+33.65)=2(3)+6(2x+4) | | 2(3x-1)+3(x+33.69)=2(3)+6(2x+4) | | 2(3x-1)+3(x+33.7)=2(3)+6(2x+4) | | 2(3x-1)+3(x+33.6)=2(3)+6(2x+4) | | 2(3x-1)+3(x+33.5)=2(3)+6(2x+4) | | 2(3x-1)+3(x+34)=2(3)+6(2x+4) | | 2(3x-1)+3(x+33)=2(3)+6(2x+4) | | 2(3x-1)+3(x+25)=2(3)+6(2x+4) |

Equations solver categories